Postgrowth imaginaries : new ecologies and counterhegemonic culture in post-2008 Spain - Pradanos, Luis I. (Contemporary Hispanic and Lusophone cultures, 2018)
An Open Access edition of this work is available on Modern Languages Open (https://www.modernlanguagesopen.org/) Postgrowth Imaginaries brings together environmental cultural studies and postgrowth economics to examine counterhegemonic narratives and radical cultural shifts sparked by the global financial crisis of 2008. A number of critical voices worldwide have emphasized that in the context of a finite biosphere, constant economic growth is a biophysical impossibility. The problem is not a lack of growth but rather the globalization of an economic system addicted to constant growth, which destroys the ecological planetary systems that support life on Earth while failing to fulfil its social promises. Post-2008 Spain offers an optimal context to investigate these cultural processes, and this book demonstrates that a transition toward what Prádanos calls 'postgrowth imaginaries'-the counterhegemonic cultural sensibilities that are challenging the growth paradigm in manifold ways-is well underway in the Iberian Peninsula today. Specifically, this book explores how emerging cultural sensibilities in Spain-reflected in fiction and nonfiction writing and film, television programs, photographs and graphic novels, op-eds, web pages, political manifestos, and socioecological movements-are actively detaching themselves from the dominant imaginary of economic growth. By approaching the counterhegemonic cultures of the crisis through environmental criticism, Postgrowth Imaginaries uncovers a whole range of cultural nuances often ignored by Iberian cultural studies. [This work] constitutes an urgent, enlightening, and empowering reflection about a crucial subject of our time. Its main focus and virtue is to provide with sound intellectual tools to think about the fundamental danger that the growth paradigm (and particularly its capitalist version) means for humanity and planet Earth. It also opens the discussion about the possibility of a "post-growth" world. [...] The book takes a special interest in studying the academic and disciplinary implications of this debate: what does it mean for humanities, cultural studies, urban studies, and, particularly for Iberian studies to take seriously the ecological crisis and the threat that the growth paradigm means? The claim is not for just a change of subjects of study in these disciplines, but moreover for a change in the way we think.' Luis Moreno-Caballud, University of Pennsylvania 'Prádanos's book will become a necessary reference for all those who will subsequently write about post-growth, environmental studies in the Spanish/Iberian context and related subjects.' Katarzyna Olga Beilin, University of Wisconsin 'The book is sure to engage Iberian and other cultural scholars. [...] throughout the book Prádanos analyses an impressively wide array of cultural productions-from the habitual novels, films, and documentaries to graphic novels and cartoons, songs, and an "audiovisual experiment," a website, a street mural in Madrid, and even an art installation made entirely of garbage-all of which call attention to the excesses and failures of the neoliberal growth fantasy.' Mònica Tomàs, ISLE: Interdisciplinary Studies in Literature and Environment